Penegakan Sanksi Hukum Terhadap Nasabah Wanprestasi Pada Koperasi Serba Usaha Bumi Raya Selong: Enforcement Of Legal Sanctions Against Customers In Default At Bumi Raya Selong Multiple Business Copperative - Ningsih, Baiq nining sulastri ningaih (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2023)
The purpose of this research is to find out the problems that will be examined in this thesis, namely to find out the enforcement of sanctions, types of engagements and actual sanctions applied to customers who default on the Bumi Raya Selong multi-business cooperative according to the Bylaws and Legislation. The research method used is normative-empirical law and the specific research used in this research is descriptive analytical research. Based on the research results, the enforcement of legal sanctions against defaulting customers in the Bumi Raya Selong multi-business cooperative according to AD-ART is that there are no strict legal sanctions given, especially in the form of criminal sanctions if members default, however, the cooperative management provides sanctions in the form of sanctions. Moral to be more precise, because it looks at the member-based statutes. Through the family system, Bumi Raya Selong’s all-business cooperative will continue to maintain friendly relations and discuss it carefully with members so that members continue to pay even though the payment is due. The types of obligations that are violated by members continue to pay even though the payment is due. The types of obligations that are violated by members of the Bumi Raya Selong multi-business cooperative who are declared to be in default include members leaving the country, members not fulfilling their obligations as members (delaying paying instalments), or members violating the rules that have been issued by the cooperative as stated in credit agreement letter.